Clinical features in liver cirrhosis patients who have experienced ischemic stroke - Kim, Kwang Min; Hwang, Jong Woon; Shim, Sang Goon (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The actual incidence of ischemic stroke in patients with liver cirrhosis remains controversial. The aim of this study was to analyze the clinical features of patients with liver cirrhosis who have experienced ischemic stroke. Materials and Methods: A retrospective analysis was performed on the medical records of 23 ischemic stroke cases who were also diagnosed with liver cirrhosis, over a 10 year period from January 2001 to December 2010. Results: Using the Child-Pugh classification system, Class B (39%) was the most common among the liver cirrhosis patients with ischemic stroke. There were six patients who presented with Class C (26%). Alcohol was analyzed as the main cause for liver cirrhosis in 14 patients (60.8%). Among the risk factors of ischemic stroke, nine of the 23 patients (39.1%) were diagnosed with obesity, and seven patients each (30.4%) were diagnosed with arrhythmia or smoking history. In total, only two patients (8.7%) had no association with any of the risk factors for ischemic stroke. Conclusion: Our results show that a comparatively high frequency of ischemic stroke occurs in patients with alcohol-induced liver cirrhosis and in patients with a less compromised liver function. In addition, it was found that most patients possessed at least one risk factor of ischemic stroke.